Neurofilament Proteins as Biomarkers to Monitor Neurological Diseases and the Efficacy of Therapies - Yuan, Aidong; Nixon, Ralph A. (Frontiers in Neuroscience, 2021)
Biomarkers of neurodegeneration and neuronal injury have the potential to improve diagnostic accuracy, disease monitoring, prognosis, and measure treatment efficacy. Neurofilament proteins (NfPs) are highly suited in this context because they are major neuron-specific components that maintain structural integrity and are sensitive to neurodegeneration and neuronal injury across a wide range of neurologic diseases. The interest in NfPs as neurological disease biomarkers has grown immensely in recent years. Low levels of NfPs are constantly released from neurons into the extracellular space and ultimately reach the cerebrospinal fluid (CSF) and blood under physiological conditions during normal development and aging. NfP levels in CSF and blood rise above normal in response to neurodegeneration and neuronal injury independently of cause. NfPs have been previously measured by invasive lumbar puncture in CSF, where these proteins are about 40-fold more concentrated than in blood. New ultra-sensitive methods allow minimally invasive measurement of the low levels of NfPs in serum or plasma. NfPs measurements have now been validated as biomarkers of neurodegeneration and neuronal injury in clinical settings to track disease onset and progression in various neurological disorders and in nervous system injuries. Such measurements have gained utility as a tool to assess responses to therapeutic interventions. Any of the five Nf subunits (NfL, NfM, NfH, INA and PRPH) may be altered in a given neuropathological condition. In familial and sporadic Alzheimer’s disease, plasma NfL levels may rise as early as 22 years before clinical onset in familial Alzheimer’s disease and 10 years before sporadic AD. The major determinants of the levels of NfPs and degradation fragments in CSF and blood are the magnitude of damaged or degenerating axons of fiber tracks, the affected axon caliber sizes and the rate of release of NfP and fragments at different stages of a given neurological diseases or condition directly or indirectly affecting CNS and PNS. Here we summarize the current understanding of NfP physiology and pathophysiology and review the value and limitations of NfP and degradation fragments as biomarkers of neurodegeneration and neuronal injury.